The canon law framework for arbitration of delictual disputes in the Roman Catholic Church of South Africa : a critical and comparative study - Muyebe, Stanslaus C. (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2005.